Blastic plasmacytoid dendritic cell neoplasm with a history of cytopenia: A case report. Issue 11 (6th May 2020) - Yan, Miao; Wang, Wensheng; Cen, Xinan; Wang, Lihong; Sun, Yuhua; Wang, Bingjie; Ou, Jinping; Nong, Lin; Ren, Hanyun; Zhu, Ping; Wang, Mangju
Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematologic malignancy arising from plasmacytoid dendritic cell precursors. The disease typically manifests in the skin, but it also evolves into a leukemic phase or can be complicated by other myeloid malignancies, especially myelomonocytic tumors. The association between these neoplasms is not fully elucidated. We report a case of BPDCN with a history of cytopenia that was supposed to be chronic myelomonocytic leukemia. The patient received intensive chemotherapy and achieved complete remission, but soon relapsed. The successive occurrence of myelomonocytic neoplasm and BPDCN is in accordance with the fact that they evolve from a common cell origin with a multilineage potential for myelomonocytic and plasmacytoid dendritic cell differentiation. This case may shed further light on the mystery of biology and the histogenesis of BPDCN.